The Role of Economic Diplomacy and Bilateral Cooperation in Promoting Foreign Investment: The Mediating Effect of Political Stability - Ana Maria Babo Sarmento; Darman; Ismail Tahir (Journal of Governance and Global Studies, 2026)
Foreign Investment Growth is influenced by a broad range of interconnected determinants that extend beyond conventional economic factors, including the implementation of Economic Diplomacy, the strength of Bilateral Cooperation, and the level of Political Stability, all of which collectively shape the attractiveness of a country's investment environment. In response to this perspective, the present study examines the influence of Economic Diplomacy and Bilateral Cooperation on Foreign Investment Growth by incorporating Political Stability as a mediating construct. The research adopted a quantitative approach involving 75 purposively selected respondents consisting of government representatives, business professionals, academics, and researchers specializing in investment, international trade, and international relations. Primary data were obtained through a five-point Likert-scale questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique implemented in SmartPLS software. The analytical framework comprised the assessment of the measurement model (outer model), evaluation of the structural model (inner model), and hypothesis testing using the bootstrapping procedure. The empirical findings reveal that Economic Diplomacy has a negative but statistically significant effect on Foreign Investment (β = -0.271; p = 0.033), while exerting a positive and statistically significant influence on Bilateral Cooperation (β = 0.723; p < 0.001). In addition, Bilateral Cooperation positively and significantly affects Foreign Investment (β = 0.378; p = 0.043). Political Stability also demonstrates a positive and statistically significant impact on Foreign Investment (β = 0.525; p = 0.002), whereas its relationship with Bilateral Cooperation is positive but does not reach statistical significance (β = 0.067; p = 0.556). The structural model explains 57.7% of the variance in Bilateral Cooperation and 36.5% of the variance in Foreign Investment. Overall, the results indicate that stronger Bilateral Cooperation and sustained Political Stability represent the principal determinants supporting Foreign Investment Growth, while Economic Diplomacy continues to exert a statistically significant direct effect despite the negative direction of its estimated relationship.